Penegakan Hukum Terhadap Pelaku Tindak Pidana Pengancaman Dengan Kekerasan Melalui Media Sosial - Kiki Andrian; Ifahda Pratama Hapsari; Dodi Jaya Wardana (Law Department, Sharia and Law Faculty., 2022)
The mechanism in this world is accelerating, one of which is entertainment based on social media sites, here and there people get influence to cause offense problems. Virtual entertainment is a medium on the website that allows clients to talk to themselves and cooperate, collaborate, share, and talk to different clients. The law controls communication between people with the aim of preventing it from happening. What is meant by problem is the way of law enforcement against demonstrations or criminal hazards as indicated by the Criminal Code, and the second is the way to enforce the Threats Act by force in accordance with the Electronic Information Transactions Act. The exploration strategy used in this test is standardization which plans to find answers to the issues that arise in it. These checks are also subject to regulations in the guidelines and are appointed by the manufacturer. By regulation, the danger of brutality is addressed in Article 335 Paragraph (1) of the Criminal Code. The Law on Information and Electronic Transactions regulates various legal guarantees for activities that use the web as a medium, exchange and use of data. In Article 29 of Law Number 11 of 2008 concerning Threats Through Information Media and Electronic Transactions, these articles are interrelated. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. Danger is a type of action that does not directly threaten or frighten someone so that it causes stress, and is awkward. savagery is that which worries something, is branded harshly.